Perancangan E-Learning Mata Pelajaran Informatika Menggunakan Google Site di SMP Negeri 1 Rao Selatan - Reza Melvita; Supratman Zakir; Liza Efriyanti; Supriadi (Jurnal Informasi, Sains dan Teknologi, 2024)
The rapid advancement of information and communication technology has opened new opportunities in education, particularly in digital-based learning. This study focuses on designing and developing an e-learning platform for Informatics subjects at SMP Negeri 1 Rao Selatan using Google Sites as a medium for online learning. The research employs the Research and Development (R&D) method with a 4D model: Define, Design, Develop, and Disseminate. The Define stage includes a needs analysis to identify requirements for online learning. The Design stage organizes e-learning content based on curriculum and standards. The Develop stage involves creating and testing the platform, while the Disseminate stage includes trials and evaluations of its effectiveness. Results show that the Google Sites-based e-learning platform enables flexible and interactive access to Informatics learning materials and assignments. It also provides an efficient tool for teachers to manage materials without requiring advanced technical skills. Positive feedback from trials highlights the platform's ease of access, interactivity, and support in enhancing material comprehension. Validity, practicality, and effectiveness tests scored 0.90, 0.95, and 0.80, respectively, indicating high reliability. These findings offer a reference for developing e-learning in other subjects and present a practical solution for distance learning in the digital era.